Tehdit Suçu (Tck. M. 106) - Kocatürk, Fatih (My University, 2015)
Tehdit, yöneltildiği kişinin iç huzurunu bozan ve güvenlik duygusunu zedeleyen bir fiildir. Dolayısıyla tehdit, kişilerin istediği gibi irade oluşturma ve oluşturduğu iradeye yönelik hareket etme hürriyetini kısıtlar. Bu sebeple 5237 sayılı Türk Ceza Kanunu tehdit fiilini “Hürriyete Karşı Suçlar” bölümünde yaptırıma bağlamış ve kişilerin karar verme ve iradi hareket etme hürriyetini koruma altına almıştır. Tez konumuzu oluşturan tehdit suçuüç ana bölümde incelenmiştir.Birinci bölümde; tehdit ve hürriyet kavramları, 765 sayılı mülga Türk Ceza Kanunu ile5237 sayılı Kanunun farkları, tehdit suçunun benzer suçlardan farkları ve suçla korunan hukuki değer izah edilmiştir. İkinci bölümde; tehdit suçunun unsurları ele alınmıştır. Üçüncü bölümde ise; kusurluluk, suçun özel görünüş şekilleri ve muhakeme usulü ile yaptırım konuları açıklanmıştır.

Threat is an action that causes to harm feeling of security and inner peace of the person who is exposed to such action. Therefore, threat limits the freedom of declaration of intention and acting upon the declared intention of the person. That is why Turkish Criminal Code numbered 5237 imposes sanction against threat in the chapter of “Crimes Against Freedom” and protects the freedom of making decision and acting of person. This Thesis examines the crime of threat which is our subject matter in three different main parts. In the first part, concepts of threat and freedom, differences between abrogated Turkish Criminal Code numbered 765 and Turkish Criminal Code numbered 5237, differences between crime of threat and offenses that are similar to threat and the legal value protected by crime have been examined. In the second part, elements of crime of threat have been examined. In the third part, issues of faultiness, special statuses of threat crime, procedure and sanction have been examined.
Keywords: Ceza Hukuku; Kamu Hukuku; Tehdit Suçu; Türkiye